TEKNIK PENINGKATAN KARAKTERISTIK FISIK BENDA COR SQUEEZE Al-Si - Elfendri - (Universitas Pasir Pengaraian, 2011)
Solidification of molten metal in squeeze casting was done under high pressure condition, it’s will produces small grains. Grains size, thickness and density depend on silicon content, molding and pouring temperature of squeeze cast parameters. The aim of this research is to analize silicon content, melt and mold temperature on thickness and density of to get a high caracteristicfhisicof thin wall squeeze castof Al-SiHydraulic pressure of 135 MPa is applied to forge molten metal of aluminum-silicon alloys. Mold temperature from 220 to 3300C, pouring temperature from 665 to 8850C and silicon content from 0,45 to 6,04% weight were considered. Thickness and density were used to indicate the caracteristic fhisic of thin wall squeeze castof Al-Si. Vernier caliper was used toruleofdimension of thin wall.The increasing of silicon content decreases thickness andincreases density of thin wall. The increasing of pouring and mold temperature increases density and decreases thickness of thin wall. Combination of the higher silicon content, melt and mold temperature produced a lowest thickness, high density and flawless thin wall squeeze cast of hot crack